Pelatihan Penyusunan Modul Ajar Berbasis Literasi, Numerasi dan Pembelajaran Berdiferensiasi dengan Aplikasi Canva bagi MGMP IPA Kota Pematangsiantar - Eva Pratiwi Pane; Melda Veby Ristella Munthe; Dewi Wahyuni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Nowadays, technological developments affect learning methods, so training is needed in creating technology-based media. Provision of teaching materials, such as the use of the Canva application by teachers, is an important part of routine activities at school. Effective teaching materials are also considered more practical and simple to use. However, not all teachers in schools use the Canva application as a tool in learning media. The purpose of Community Service (PkM) through this technical training is to improve the knowledge and skills of teachers who are members of the Pematangsiantar City IPA MGMP in designing learning media based on literacy, numeracy, and differentiated learning. The PkM method is carried out with an interactive and socialization approach that aims to build motivation, through the stages of implementation planning, as well as work procedures, namely the planning, action, observation, and evaluation stages. This Canva technical training was held in August 2024 with the participation of 30 participants. The PkM activity produced quite good achievements, where in each instructional objective there were changes in indicators that showed satisfactory development. Participants had a good understanding of the Canva application and acknowledged that the application was useful in helping to compile learning modules. Based on technical factors and supporting factors, it is known that this technical training brings changes to the knowledge and skills of participants.